Asymmetric, amphiphilic RGD conjugated phthalocyanine for targeted photodynamic therapy of triple negative breast cancer - Rui Li; Yiming Zhou; Yijia Liu; Xingpeng Jiang; Wenlong Zeng; Zhuoran Gong; Gang Zheng; Desheng Sun; Zhifei Dai (Signal Transduction and Targeted Therapy, 2022)
Abstract Targeted photodynamic therapy (TPDT) is considered superior to conventional photodynamic therapy due to the enhanced uptake of photosensitizers by tumor cells. In this paper, an amphiphilic and asymmetric cyclo-Arg-Gly-Asp-d-Tyr-Lys(cRGDyK)-conjugated silicon phthalocyanine (RSP) was synthesized by covalently attaching the tripeptide Arg-Gly-Asp (RGD) to silicone phthalocyanine in the axial direction for TPDT of triple-negative breast cancer (TNBC). RSP was characterized by spectroscopy as a monomer in physiological buffer. Meanwhile, the modification of RSP with RGD led to a high accumulation of the photosensitizer in TNBC cells overexpressing ανβ3 integrin receptors which can bind RGD, greatly reducing the risk of phototoxicity. In vitro photodynamic experiments showed that the IC50 of RSP was 295.96 nM in the 4T1 cell line, which caused significant apoptosis of the tumor cells. The tumor inhibition rate of RSP on the orthotopic murine TNBC achieved 74%, while the untargeted photosensitizer exhibited no obvious tumor inhibition. Overall, such novel targeted silicon phthalocyanine has good potential for clinical translation due to its simple synthesis route, strong targeting, and high therapeutic efficacy for TPDT treatment of TNBC.